2022
DOI: 10.21203/rs.3.rs-1311742/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linkage to HIV care following HIV self-testing among men: systematic review of quantitative and qualitative studies from six countries in sub-Saharan Africa

Abstract: Gender disparities are pervasive throughout the HIV care continuum in sub-Saharan Africa, with men testing, receiving treatment, and achieving viral suppression at lower rates, and experiencing mortality at higher rates, compared with women. HIV self-testing (HIVST) has been shown to be highly acceptable among men in sub-Saharan Africa. However, evidence on linkage to HIV care following a reactive HIVST result is limited. In this systematic review, we aimed to synthesize the quantitative and qualitative litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similar findings have been reported in resource-limited settings, where personal and structural barriers including lack of emotional readiness, transport costs, long waiting times in public health care facilities, privacy concerns, and stigma remain persistent and continue to deter men from accessing HIV services (Hlongwa et al, 2020; Rhead et al, 2019). Men with reactive HIV self-test results have recently been reported to have similar barriers to be linked to HIV care (Hlongwa et al, 2022). A study conducted in a comparable setting indicated that due to fear of testing positive for HIV, some men believed that once their HIV-positive status was revealed, their wives or partners would abandon them or refuse them sex, suggesting an important indication of a lack of emotional readiness (Mambanga et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in resource-limited settings, where personal and structural barriers including lack of emotional readiness, transport costs, long waiting times in public health care facilities, privacy concerns, and stigma remain persistent and continue to deter men from accessing HIV services (Hlongwa et al, 2020; Rhead et al, 2019). Men with reactive HIV self-test results have recently been reported to have similar barriers to be linked to HIV care (Hlongwa et al, 2022). A study conducted in a comparable setting indicated that due to fear of testing positive for HIV, some men believed that once their HIV-positive status was revealed, their wives or partners would abandon them or refuse them sex, suggesting an important indication of a lack of emotional readiness (Mambanga et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons given for not linking to confirmatory testing suggest potential misinterpretation of the result or misunderstanding about the need to perform a confirmatory HIV test, highlighting the need to improve messaging around HIVST, in particular when HIV self-testing policies will be scaled-up. For those who did confirmatory testing and were confirmed HIV positive, initiation of antiretroviral treatment was almost systematic, showing good linkage to care after confirmatory testing, as observed in many HIVST studies in sub-Saharan Africa [49][50][51].…”
Section: Discussionmentioning
confidence: 53%
“…However, social network strategies showed significant improvements in the uptake of testing, which positively impacted linkage. In addition, peerbased interventions, including communication links, social support, and monetary incentives, increased the likelihood of linkage to care [65,66]. The comparable linkages demonstrated the reliability and potential of the social network strategy in improving HIV care services, not only in HIV testing.…”
Section: Discussionmentioning
confidence: 86%